2018
DOI: 10.1038/s41372-018-0086-y
|View full text |Cite
|
Sign up to set email alerts
|

Early low-dose hydrocortisone: is the neurodevelopment affected?

Abstract: Type of investigation Prognosis; exploratory secondary analysis of an interventional randomized controlled trial. Question In extremely preterm infant (<28 weeks), is early low-dose hydrocortisone compared to placebo associated with neurodevelopmental impairment at 2 years of age? Methods Patients Surviving infants enrolled in the PREMILOC trial conducted in France between 2008 and 2014. Intervention Double-blind, multicenter, randomized, placebo-controlled trial of infants born between 24 0/7 weeks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Follow-up studies revealed no increase in long-term adverse neurodevelopmental outcomes. 39 , 40 Given the known risks and only potential benefits of postnatal steroids, the decision to administer steroids, as well as the optimal dosage and timing, remains challenging and unclear. Identifying biomarkers or genes that confer a greater likelihood of improved respiratory status with postnatal steroid administration would be a worthwhile contribution.…”
Section: Anti-inflammatoriesmentioning
confidence: 99%
“…Follow-up studies revealed no increase in long-term adverse neurodevelopmental outcomes. 39 , 40 Given the known risks and only potential benefits of postnatal steroids, the decision to administer steroids, as well as the optimal dosage and timing, remains challenging and unclear. Identifying biomarkers or genes that confer a greater likelihood of improved respiratory status with postnatal steroid administration would be a worthwhile contribution.…”
Section: Anti-inflammatoriesmentioning
confidence: 99%